2006
DOI: 10.1179/acb.2006.025
|View full text |Cite
|
Sign up to set email alerts
|

Coriander Anaphylaxis in a Spice Grinder With Undetected Occupational Allergy

Abstract: The clinical manifestations in temporal relationship to ingestion of coriander and handling of coriander and/or fenugreek, the positive specific IgE results, skin tests and basophil activation assays support the diagnosis of allergy to both spices. History suggests sensitization by occupational exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…20 In the case of fenugreek, the potential cross-reactivity with peanut, responsible for most of the foodrelated fatal allergic incidents in the United States, should be taken into account. 31 Physicians might include fenugreek in the diagnostic program for patients with peanut allergy and advise them to avoid Indian-style food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In the case of fenugreek, the potential cross-reactivity with peanut, responsible for most of the foodrelated fatal allergic incidents in the United States, should be taken into account. 31 Physicians might include fenugreek in the diagnostic program for patients with peanut allergy and advise them to avoid Indian-style food.…”
Section: Discussionmentioning
confidence: 99%
“…18 There have, however, been reports of patients without birch allergy who have reacted to the mixed-spice blend curry. 19,20 Indian-style meals often contain the legume fenugreek, which may cross-react with major allergens such as peanut, soy, and lupin.…”
Section: Discussionmentioning
confidence: 99%
“…Ebo et al 37 observed anaphylaxis effects in one patient. The patient developed urticaria, angio-edema, rhinoconjuctivitis and bronchospasm during handling of coriander and fenugreek.…”
Section: Adverse Effects and Safety Issuesmentioning
confidence: 98%
“…[18][19][20][21] The first such report described a patient who experienced rhinorrhea, wheezing, and syncope after inhalation of fenugreek seed powder and another who developed numbness of the head, facial angioedema, and wheezing after application of fenugreek paste to the scalp. Patients with an allergy or hypersensitivity to fenugreek, its constituents, or plants in the Fabaceae family should not consume fenugreek.…”
Section: Dosagementioning
confidence: 99%
“…1 It should be avoided in patients allergic to chickpeas, peanuts, and coriander due to possible cross-reactivity. 20 Occupational asthma caused by fenugreek has also been reported. [18][19][20][21] The first such report described a patient who experienced rhinorrhea, wheezing, and syncope after inhalation of fenugreek seed powder and another who developed numbness of the head, facial angioedema, and wheezing after application of fenugreek paste to the scalp.…”
Section: Dosagementioning
confidence: 99%